Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I get stuck at the following question:

Consider the matrix $A$ = $\begin{bmatrix} 0 & 2 & 0 \\ 1 & 1 & -1 \\ -1 & 1 & 1\\ \end{bmatrix}$

Find $A^{1000}$ by using the Cayley-Hamilton theorem.

I find the characteristic polynomial by $P(A) = -A^{3} + 2A^2 = 0$ (by Cayley-Hamilton) but I don't see how to find $A^{1000}$ by this characteristic polynomial.

share|cite|improve this question
up vote 26 down vote accepted

Your formula tells you, after you multiply through by $A^{997}$, that $$A^{1000}=2A^{999}.$$ Similarly, $$2A^{999}=4A^{998}.$$

This process can be repeated to find $A^{1000}$ in terms of $A^2$, which you can then compute.

share|cite|improve this answer
Cute! Mathematical Cuteness buys a +1 on my books! – Robert Lewis Apr 5 '14 at 22:44
Answered my question, thanks a lot! – surfer1311 Apr 5 '14 at 23:11

There is another way of approaching this.

You could divide $x^{1000}$ by the characteristic polynomial:

$x^{1000} = (-x^3+2x^2)Q+R$ where $R$ is a polynomial of degree less than 3 with unknown coefficients.

write down $R=ax^2+bx+c$ and evaluate $R$ at the roots of the characteristic polynomial.

Meaning, write down $\lambda^{1000}=a\lambda ^2+b\lambda+c$


$\xi^{1000} = a\xi ^2+b\xi+c$


$\rho^{1000} = a\rho ^2+b\rho+c$

where $\lambda$ and $\xi$ and $\rho$ are roots of the characteristic polynomial. as you can see, $Q$ wont matter because it is multiplied by zero.

Do this to find the coeffiecents of the remainder, $R$.

after you have done that, insert $x=A$ to get $A^{1000}=aA^2+bA+c$ with the coeffiecents $a,b,c$ that you found.

Edit: The problem here, is that you have a double root, so you need to use the derivative as well.

Full answer:

divide $x^{1000}$ by $(-x^3+2x^2)$ to get:

$x^{1000} = (-x^3+2x^2)Q+ax^2+bx+c$ where $Q$ is some polynomial unknown to us.

the roots of the char. polynomial are $0,2$. put $x=0$ to get:

$0^{1000}=0=0*Q+c=c$ so $c=0$.

now derive $x^{1000} = (-x^3+2x^2)Q+ax^2+bx$ to get:

$1000x^{999}=(-3x^2+4x)Q+Q'(-x^3+2x^2)+2ax+b$ and insert $x=0$ again t oget:

$1000*0^{999} = 0 =b$ meaning $b=0$.

Now back to our original formula with $b=c=0$:

$x^{1000} = (-x^3+2x^2)Q+ax^2$

Insert $x=2$ to get:

$2^{1000} = 4a$ meaning $a=2^{998}$.

Now our original formula looks like $x^{1000} = (-x^3+2x^2)Q+2^{998}x^2$

Inserts $x=A$ to get:

$A^{1000} = 2^{998}A^2$

share|cite|improve this answer
Would you like me to write down entire solution for you? or are you fine for now :)? – Oria Gruber Apr 5 '14 at 22:55
Wrote it down anyway. – Oria Gruber Apr 5 '14 at 23:07
+1 very nice! :-) – Ant Apr 6 '14 at 14:11

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $$ \expo{At}=\alpha\pars{t} + \beta\pars{t}A + \gamma\pars{t}A^{2} $$

$$\dot{\alpha}\pars{t} + \dot{\beta}\pars{t}A + \dot{\gamma}\pars{t}A^{2} =A\expo{At} =\alpha\pars{t}A + \beta\pars{t}A^{2} + \gamma\pars{t}\ \overbrace{A^{3}}^{2A^{2}}\,, \quad \left\lbrace% \begin{array}{l} \alpha\pars{0} = 1 \\[1mm] \beta\pars{0} = \gamma\pars{0} = 0 \end{array}\right. $$

$$ \dot{\alpha}\pars{t} = 0\,,\quad \dot{\beta}\pars{t} = \alpha\pars{t}\,,\quad \dot{\gamma}\pars{t} = \beta\pars{t} + 2\gamma\pars{t} \quad\imp\quad \left\lbrace% \begin{array}{rcl} \alpha\pars{t} & = & 1 \\[1mm] \beta\pars{t} & = & t \\[1mm] \gamma\pars{t} & = & {\expo{2t} - 2t - 1 \over 4} \end{array}\right. $$

$$ \expo{At} = 1 + tA + {\expo{2t} - 2t - 1 \over 4}\,A^{2} $$

\begin{align} A^{1000} &= \left.\totald[1000]{\pars{\expo{At}}}{t}\right\vert_{t = 0} =\left. {A^{2} \over 4}\, \totald[1000]{\bracks{\expo{2t} - 2t - 1}}{t}\right\vert_{t = 0} ={A^{2} \over 4}\,2^{1000} \end{align} $$ \boxed{\vphantom{\Huge {A \over B}}\quad\color{#00f}{\large A^{1000} = 2^{998}\ A^{2}}\quad} $$

share|cite|improve this answer
Nice and innovative. Only one query: why $e^{At}=\alpha(t)+\beta(t)A+\gamma(t)A^2$, why not further more terms? @Felix Marin – Anjan3 Sep 8 '14 at 7:57
@AnjanDebnath Because any term $A^{k}$, with $k>2$, is a linear combination of $A^{0},A$ and $A^{2}$: $A$ satisfies its characteristic equation which is a third degree polynomial in $A$. See Cayley–Hamilton theorem. – Felix Marin Sep 8 '14 at 12:57
upps !! My bad. didn't noticed – Anjan3 Sep 8 '14 at 17:07

$$A^{1000}= A(A^3)^{333}=A (-2A^2)^{333}=(-2)^{333}A^{667}=\cdots$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.